Monks and Educational Welfare Management - (ทองมา), พระมหาปริญณภัสทร์ รุจิธมฺโม; ศุภเลิศ, ปฐมพงศ์ (Journal of Educational Review Faculty of Education in MCU, 2018)
The Buddhist monks have given assistance to people served courtesy Lend a hand to people in society since the Buddha’s time until now. In Thailand, the monks have also worked alongside with government sectors to help people since the Sukhothai period up to now. The educational assistance is a monks’ duty since it was specified in the Sangha Act. The educational welfare management of the Sangha is to support physical and mental wellness among children and youths.